Development and characterisation of cooked inlaid sausages with fillet and mechanically separated meat of Nile tilapia (Oreochromis niloticus) - Cavenaghi-Altemio, Angela Dulce; Zitkoski, João Luiz; Fonseca, Gustavo Graciano (Journal of Fisheries, 2022)
The limited consumption of fish is due to a limited availability of products based on this type of meat. Therefore, innovation and development of products that meet consumers’ preferences are essential. The aim of this work was to develop and characterize cooked inlaid sausages prepared with fillet and mechanically separated Nile tilapia (Oreochromis niloticus) meat (MSM). Three sausages types were considered, F1 (100% MSM), F2 (50% MSM, 50% fillet) and F3 (25% MSM, 75% fillet). Microbiological quality of the raw materials and products obtained were within the standard limits. F1 had the lowest protein (34.68%) and the highest lipid (2.88%) contents. F1 and F2 had the highest luminosity L*, which was related to the MSM composition, as the L* was higher as the percentage of MSM increased in the formulation. The shear strength was higher for F2 (18.55 N) and lower for F1 (6.43 N) and differed among sausages types. The F2 sausages presented a better acceptability regarding the sensory attributes evaluated, with acceptation indexes of 88.00, 85.55, and 84.66% for flavour, texture, and odour respectively. This finding indicates that this formulation would be very well accepted in the market if available for commercialisation.